Photocatalytic oxidation of acetaminophen using carbon self-doped titanium dioxide - Mark Daniel G. de Luna; Justin Chun-Te Lin; Mary Jane N. Gotostos; Ming-Chun Lu (Sustainable Environment Research, 2016)
A new carbon self-doped (C-doped) TiO2 photocatalyst was synthesized by sol–gel method, in which titanium butoxide was utilized because of its dual functions as a titanium precursor and a carbon source. The effects of calcination temperature from 200 to 600 °C on the photocatalytic activity towards acetaminophen (ACT, which was used as a model persistent organic pollutant) under visible light were examined. The effects of temperature on the structure and physicochemical properties of the C-doped TiO2 were also investigated by X-ray diffraction, BET measurement, X-ray photoelectron spectroscopy, and scanning electron microscopy. The specific surface area of the as-doped TiO2 declined as the crystal size increased with increasing calcination temperature. Only amorphous TiO2 was present at 200 °C, while an anatase phase was observed between 300 and 500 °C. Both anatase and rutile phases were observed at 600 °C. Photocatalytic activity increased as the calcination temperature initially increased from 200 to 300 °C but it decreased as the calcination temperature further increased from 400 to 600 °C. The highest ACT removal of 94% with an apparent rate constant of 5.0 × 10−3 min−1 was achieved using the new doped TiO2 calcined at 300 °C, which had an atomic composition of 31.6% Ti2p3, 50.3% O1s and 18.2% C1s.